Termites assemblages in oil palm plantation in Sarawak, Malaysia - King, Patricia Jie Hung (2012)
Termite is a vital component in a healthy forest or agriculture ecosystem. The diversity of termite species reflects the overall ecosystem production and health. This study aimed to evaluate the diversity of termite in Sarawak agriculture peat zone and to identify the key morphometric characters in species identification. Belt transects sampling was carried out in two studies sites. Individual termites were carefully observed, measured and 15 morphometric characters were identified as important in species identification. At the present stage, this study had found six genera which can be further categorized into thirteen termite species. The wood feeder termite has been identified to be the most dominant species and Rhinotermitidae are the most species-rich family. This is in contrast with the conserved forest where soil-feeding termites are the most diverse group of termites. Among the species identified in the studied sites were the Coptotermes curvignathus, C. sepangensis, C. gestroi, Parrhinotermes aequalis, Schedorhinotermes brevialatus, S. javanicus, S. sarawakensis, Pericapritermes dolichocephalus, P. latignathus, Nasutitermes havilandi, N. longinasoides, N. matangensiformis and Havilanditermes atripennis. The study showed that agricultural practice has some extend of repercussion on termite assemblage structure.